O papel dos credores no direito falimentar: uma análise histórica e à luz de certos órgãos - Vasconcelos, Adriana Paiva (2013)
The purpose of this paper is to analyze the role of the creditors in Brazilian Bankruptcy Law, since the first rule enacted up to the current one, in accordance with certain bodies and their way of action. Take a glance about the role of the creditors at the main bankruptcy laws. This study be moved by verifying the possibility -or its absence - for the creditors action in the reorganization of the crisis of the debtor and the ways it can be implemented, as the participation in certain bodies in the bankruptcy procedure. Inspired on the affirmation regarding the existing of a pendulum dualism in the bankruptcy Brazilian law made by Fábio Konder Comparato, this paper intends, in a simple way, to verify the preponderance of absence of creditor´s right in this area of Law. For this, it is a must the investigation of the relevant Brazilian old and current laws that deals with this matter, in order to make possible to explore how creditors may act, at each rule, and it there was, until the current legislation, an evolution or involution of their rights. A research of the institutes disciplined be made with the purpose to check in each regulation, the study about the existence and way of acting of similar bankruptcy bodies and their characteristics in each moment. Further to the legal rules, doctrine was verified. At last, jurisprudence was examined in order to analyze real cases and the use of the rules existence based on the action of the creditors